Substance - Unsubstance - Graps Grafs, Jan Joonas; Gulk, Albert; Helme, Sirje; Jaanisoo, Jaan; Juske, Ants; Kalm, Anu; Kask, Jüri; Kelomees, Raivo; Keskküla, Ando; Komissarov, Eha; Krull, Hasso; Kurm, Rainer; et al. (Tallinn : Soros Center for Contemporary Arts, 1994)
Destudio ; Graps Grafs, Jan Joonas ; Li, Pier ; Gulk, Albert ; Jaanisoo, Jaan ; Kalm, Anu ; Kalve, Toomas ; Kask, Jüri ; Kelomees, Raivo ; Kurm, Rainer ; Saks, Jaak ; Lapin, Leonhard ; Lestberg, Ly ; Pãrnamets, Tairo ; Linnap, Eve ; Linnap, Peeter ; Meel, Raul ; Muru, Urmas ; Ojaver, Jüri ; Ole, Kaido ; Pere, Peeter ; Prääts, Rait ; Raidmets, Toivo ; Senka, Sven ; Seppet, Ahti ; Tammelaan, Tea ; Tolts, Andres ; Toomik, Jaan ; Viljus, Mart ; Vint, Aili ; Vãllik, Martin
biog., bibliog. per kunstenaar [1 p.]
Engels & Ests
Substance - Unsubstance / Aine - Aineta, Soros Center for Contemporary Arts, Estonia, Tallinn, The 1st Annual Exhibition, 30.11 - 19.12.1993, Tallinn Art Hall, Tallinn ; Gallery of the Tallinn Art Hall, Tallinn; Luum Gallery, Tallinn ; Sammas Gallery, Tallinn ; Hirvepark
kunstcatalogus
Keywords: Estland